Dual-Genotype Diffuse Low-Grade Glioma: Is It Really Time to Abandon Oligoastrocytoma As a Distinct Entity?. Issue 5 (17th April 2017) - Barresi, Valeria; Lionti, Simona; Valori, Laura; Gallina, Giovanna; Caffo, Maria; Rossi, Sabrina
Abstract : We report a unique case of dual-genotype oligoastrocytoma characterized by IDH2 gene mutation. The tumor was resected from the temporal lobe of a 25-year-old man. At histological examination with hematoxylin and eosin stain, it showed distinct oligodendroglial and astrocytic areas. The former retained alpha-thalassaemia/mental retardation X-linked (ATRX) immuno-expression and had absent staining for p53, while the latter had ATRX loss and p53 over-expression. Molecular analyses were separately assessed in the 2 tumor components. Gene sequencing disclosed IDH2 mutation in both, whereas oligodendroglial, but not astrocytic areas, had 1p/19q codeletion and telomerase reverse transcriptase promoter mutation. Distinction of dual-genotype oligoastrocytoma from oligodendroglioma and astrocytoma might be clinically relevant for prognosis and therapy. Because most studies that investigated the molecular phenotype of oligoastrocytomas have focused on IDH1 R132H mutated cases, we suggest further analyses on diffuse gliomas with heterogeneous (astrocytic and oligodendroglial) morphology before oligoastrocytoma is dismissed as a distinct nosological entity.